Comb Detection for Measuring Shear Wave Propagation - Lee, Hyoung-Ki (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2023)
Plane wave compounding (PWC) is widely used to measure the propagation of shear waves. Implementing PWC on most commercial ultrasound scanners is challenging because all channel (>128) data must be processed or transferred to the host computing unit in real time. Comb detection transmits multiple focused beams simultaneously and results in a reduced number of receive lines to be processed in parallel. These comb beams are scanned laterally to acquire receive lines at different lateral positions in order to obtain data over a large region of interest (ROI). One of the potential issues with using multiple simultaneously transmitted beams is the issue of crosstalk between the beams. Crosstalk is analyzed through simulated beam patterns, simulated B-mode images, and motion data from shear wave elastography (SWE) experiments. Using a Hamming window on transmit and receive can suppress crosstalk to 1.2% root-mean-square error (RMSE, normalized RMSE to the peak magnitude of the reference signal) for shear wave motion signals. Four comb beams with three laterally scanned locations cover almost the entire field of view (FOV) and achieve the same frame rate as PWC with three angles. Phantom and in vivo studies demonstrate comparable motion data of comb detection to PWC in terms of motion signal quality and measured phase velocity. In addition, comb detection provides motion with lower noise and stronger signals than PWC, which is believed to be due to the advantages of transmitting focused beams rather than plane waves (PWs)